Community participation and neighborhood factors associated with physical and mental health among low-income mothers in the United States. Issue 3 (27th May 2021) - McCloskey, Rebecca J.; Maguire-Jack, Kathryn
ABSTRACT: Religious and social participation and neighborhood factors have been associated with health outcomes. Because depression and physical health problems are common among mothers, we sought to understand whether participation would be associated with more favorable health outcomes when accounting for neighborhood factors: disorder, social cohesion, and informal social control. Using Fragile Families and Wellbeing Study data (N = 2, 926) we ran logistic regression models to estimate the relationships between depression, physical health, community participation, and perceived neighborhood factors. Neither religious nor social participation was significant in the models. However, the odds of meeting the criteria for depression were 1.20 times (95% CI [1.05, 20 1.37]) higher among mothers' reporting higher neighborhood disorder. Neighborhood social cohesion was inversely associated with depression; higher neighborhood disorder was associated with decreased favorable health. Findings provide further evidence that interpersonal factors may be insufficient to overcome the detrimental effects of community-level factors.